2011
DOI: 10.1111/j.1751-7893.2011.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Burdens and difficulties experienced by caregivers of children and adolescents with schizophrenia-spectrum disorders: a qualitative study

Abstract: Additional work is needed to learn more about the challenges that caregivers of youth with schizophrenia-spectrum disorders are facing, as well as to develop empirically based strategies for helping these caregivers and their dependents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 27 publications
3
33
0
1
Order By: Relevance
“…[11][12][13][14] This literature has drawn attention to multiple burdens associated with caring for a family member who has a mental illness including: financial challenges, physical and psychological demands associated with care-giving and advocacy, disruption of household routines, restriction of social activities, impaired relationships with others outside of the family, emotional distress associated with difficult and at times bizarre behaviours, as well as secondary distress associated with the reactions of others both within and outside of the family. Several studies [15][16][17] have also drawn attention to an ongoing pattern of grief associated with parenting a child with mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] This literature has drawn attention to multiple burdens associated with caring for a family member who has a mental illness including: financial challenges, physical and psychological demands associated with care-giving and advocacy, disruption of household routines, restriction of social activities, impaired relationships with others outside of the family, emotional distress associated with difficult and at times bizarre behaviours, as well as secondary distress associated with the reactions of others both within and outside of the family. Several studies [15][16][17] have also drawn attention to an ongoing pattern of grief associated with parenting a child with mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…In the search for mental health services that meet the needs of children or adolescents, difficulties related to accessibility were observed, as access to mental health services becomes particularly difficult when children are having seizures (11)(12) . Difficulties were also found regarding the suitability of the services when it comes to safety and the impact of negative experiences of children/adolescents and family members with health staff (10) .…”
Section: Discussionmentioning
confidence: 99%
“…The future was also mentioned, especially regarding options for employment for the mentally ill (10,18) and the well-being of relatives, including access to health care services by spouses and other children, as well as the maintenance of household routines (12) .…”
Section: Discussionmentioning
confidence: 99%
“…Ghosh & Greenberg, 2009;Möller-Leimkühler & Wiesheu, 2012;Papastavrou et al, 2010), compared to studies that explore caregiver burden of children or adolescents with mental health problems. In a rare study of caregiver burden of carers with adolescents who experience schizophrenia, Knock et al (2011) point out that 'Despite the recent increase in research exploring caregiver burdens for adults with schizophrenia, virtually no studies of caregivers of children and adolescents with schizophrenia exist ' (p.350). It must be acknowledged that schizophrenia in adolescents is uncommon and subsequently, such a study is equally uncommon in the literature.…”
Section: The Parent's Experience Of Their Child's Mental Illnessmentioning
confidence: 99%
“…To date, the literature has tended to focus on the first two domains such as the impact of psychiatric hospitalisation on the adolescent (Lopez, 2000;Thibeault et al, 2010), the impact of the adolescent's difficulties on their parents (Faust & Scior, 2008;Knock et al, 2011) or the impact of working with this population on staff (Dean et al, 2010;van Kessel et al, 2012). Little literature could be found that could be said to investigate the third domain in the context of adolescent inpatient units.…”
mentioning
confidence: 99%